Factores de riesgo ante la reincidencia delincuencial de los adolescentes recluidos en la Corporación para la atención integral de menores de Colombia (2023)
This research addresses the risk factors Risk factors for criminal recidivism of adolescents held in the Comprehensive Care Center for Minor Offenders of La Guajira. In this way, the objective is to identify the risk factors for criminal recidivism of adolescents held in the Comprehensive Care Center for Minor Offenders of La Guajira. Consequently, to obtain a detailed analysis of the data, a characterization of the risk factors and the application of the evaluation battery of Risk Factors for criminal recidivism of adolescents held in the Comprehensive Care Center for Minor Offenders is carried out. la Guajira CAIMEC, which allows the identification and categorization of risk factors and their individual dimension and family and social environment.